2009
DOI: 10.3201/eid1503.081410
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Avian Influenza Virus (H5N1) Outbreak in Captive Wild Birds and Cats, Cambodia

Abstract: From December 2003 through January 2004, the Phnom Tamao Wildlife Rescue Centre, Cambodia, was affected by the highly pathogenic influenza virus (H5N1). Birds from 26 species died. Influenza virus subtype H5N1 was detected in 6 of 7 species tested. Cats from 5 of 7 species were probably infected; none died.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 12 publications
(9 reference statements)
1
18
0
Order By: Relevance
“…While the majority of LPAIV isolates from free-ranging birds have originated from waterfowl (Stallknecht & Shane, 1988), both LPAIV and HPAIV have been isolated from passerine birds throughout a wide geographic area encompassing portions of Europe, Australia, North America, Africa, Asia, and the Middle East. Examples of these isolations have included swabs collected from house sparrows in Hungary and European starlings in Israel and Australia (Romváry et al, 1976, in Stallknecht & Shane, 1988Lipkind et al, 1979;Amin et al, 1980;Boudreault et al, 1980;Boudreault & LeComte, 1981;Cross, 1986;Nestorowicz et al, 1987;Kwon et al, 2005;Gronesova et al, 2008;Desvaux et al, 2009). In addition, cloacal swabs collected from 22 passerine species throughout the USA from 2005 to 2008 were AIV-positive by RT-PCR, with an approximate prevalence of 1% among passerines (Fuller et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…While the majority of LPAIV isolates from free-ranging birds have originated from waterfowl (Stallknecht & Shane, 1988), both LPAIV and HPAIV have been isolated from passerine birds throughout a wide geographic area encompassing portions of Europe, Australia, North America, Africa, Asia, and the Middle East. Examples of these isolations have included swabs collected from house sparrows in Hungary and European starlings in Israel and Australia (Romváry et al, 1976, in Stallknecht & Shane, 1988Lipkind et al, 1979;Amin et al, 1980;Boudreault et al, 1980;Boudreault & LeComte, 1981;Cross, 1986;Nestorowicz et al, 1987;Kwon et al, 2005;Gronesova et al, 2008;Desvaux et al, 2009). In addition, cloacal swabs collected from 22 passerine species throughout the USA from 2005 to 2008 were AIV-positive by RT-PCR, with an approximate prevalence of 1% among passerines (Fuller et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we investigated whether HPAIV H5N1 infection can occur via the gastrointestinal tract in cats. We used cats as a mammalian infection model because fatal disease caused by natural HPAIV H5N1 infections has been reported in domestic cats, leopards, tigers, and other different species of wild cats in Asia 5,6,9,11,16 and Europe. 14,17 Infection experiments revealed that HPAIV H5N1 attaches in the lungs of infected cats predominantly to alpha 2AE3 sialoglycan residues present at the surface of type II pneumocytes and alveolar macrophages in the lower respiratory tract, a pattern which most closely resembles that seen in human lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Based on phylogenetic and epidemiological analysis, many influenza viruses have also been directly transmitted between avian species, between avian and nonhuman mammals, and between different mammalian species ( Figure 2B). Outbreaks due to interspecies jumping include the avian H5N1 outbreaks in zoos involving different mammalian species [62] and in cats [63], equine H3N8 and avian H3N2 outbreaks in dogs [64], and the avian H3N8 outbreak in seals [65].…”
Section: Interspecies Transmission Of Influenza Virusesmentioning
confidence: 99%